The fungal gut microbiota in pediatric-onset multiple sclerosis - Mok, Nelson; Knox, Natalie C.; Zhu, Feng; Arnold, Douglas L.; Bar-Or, Amit; Bernstein, Charles Noah; Bonner, Christine; Forbes, Jessica D.; Graham, Morag; Marrie, Ruth Ann; O’Mahony, Julia; Yeh, E. Ann; et al. (Frontiers in Microbiology, 2024)
Evidence suggests that the gut microbiome may play a role in multiple sclerosis (MS). However, the majority of the studies have focused on gut bacterial communities; none have examined the fungal microbiota (mycobiota) in persons with pediatric-onset multiple sclerosis (POMS). We examined the gut mycobiota in persons with and without POMS through a cross-sectional examination of the gut mycobiota from 46 participants’ stool samples (three groups: 18 POMS, 13 acquired monophasic demyelinating syndromes [monoADS], and 15 unaffected controls). Using metataxonomic sequencing of the fungal internal transcribed spacer region 2, the fungal profiles were compared between participants using visualizations, statistical tests, and predictive analysis. While the mycobiome α- (Shannon and inverse Simpson indices) and β-diversity differed across the three groups [analysis of variance (ANOVA), p < 0.05], further post-hoc analysis of the β-diversity identified a difference between monoADS vs. POMS participants [p = 0.005 (adjusted)]. At the genus level of taxonomy, 7 out of 10 of the majority of abundant genera were similar among all three groups, with Saccharomyces spp. and Candida spp. being in the highest abundance. The Agaricus genus was especially high in POMS participants, dominated primarily due to the species Agaricus bisporus (widely consumed as white button mushrooms). The commonality of high abundance fungi found in our cohort suggests a possible connection to diet. Predictive modeling of differential abundance associated with Candida albicans, Cyberlindera jadinii, and Fusarium poae revealed that these fungi were strongly associated with the POMS participants. Our study provides novel insight into the fungal gut mycobiota in POMS. While findings indicate that the gut mycobiome of participants with POMS may largely comprise fungi considered transient from the diet, the differential predictive analysis suggested rare or under-detected fungal markers being of potential importance, warranting consideration in future mycobiome-MS-related studies.